IoT architectures, models, and platforms for smart city applications - Chowdhry, Bhawani Shankar; Shaikh, Faisal Karim; Mahoto, Naeem Ahmed, 1983- (Advances in computer and electrical engineering (ACEE) book series., 2020)
"This book examines the major aspects of the internet of things and how this platform can enhance smart cities by securing innovative solutions for their challenges rather than using basic off-the-shelf solutions"--